Critical Discourse Analysis of Language on Facebook used in Birthday Wishes by Generation Z - Sapkota, Chet Narayan (Madhyabindu Journal, 2022)
The present study analyzes the language used in birthday wishes and how social power is legitimized by Generation Z. It examines the relationship between the language used in birthday wishes messages, events and practices, as well as social and cultural structure and relations to comprehend how power relations influence the ideological formation of the texts. The status notification of 10 Facebook friends belonging to Generation Z is chosen in the constant experimental sampling method. The analysis was conducted following Fairclough's Critical Discourse Analysis with the critical linguistic approach. The study shows that the language of birthday wishes on facebook is dominated by the function of the language as a medium of selfexpression and interaction. The use of informal language influences language proficiency, language variation of gender, and socio-culture practices are a common form of text production.